Resettable skin interfaced microfluidic sweat collection devices with chemesthetic hydration feedback - Jonathan T. Reeder (Nature Communications, 2019)
Wearables capable of collecting and analyzing sweat are of interest for athletics and health monitoring. Here, the authors report a resettable microfluidic platform comprising soft pumps and valves that provides triggered release of chemesthetic agents to alert the user of excessive sweat loss.